Code-Switching in EFL Classrooms: A Tool for Comprehension or a Hindrance in Fluency - Rengur, Zul Aini; Putri, Prisna Aswarita; Fatima, Fatima; Mansur, Nurfauziah; Zulfikri, Zulfikri; Kuliahana, Ana; Fatimawali, Fatimawali (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2025)
This study explored the dual role of code-switching in English as a Foreign Language (EFL) classrooms, examining whether it functioned more as a tool to support comprehension or as a hindrance to fluency development. Employing a qualitative descriptive design, the research involved three English teachers and ten intermediate-level students in a bilingual educational context. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analysed thematically. Findings revealed that when used strategically and sparingly, code-switching served as an effective pedagogical scaffold, enhancing comprehension, reducing learners’ anxiety, and fostering confidence—particularly among lower-proficiency students. Teachers reported that occasional use of the students’ first language (L1) maintained lesson flow and facilitated understanding of complex material. However, excessive reliance on code-switching was found to limit students’ opportunities to practice English, foster dependency on L1, and impede the development of fluency and communicative competence. These findings underscored the need for a balanced and principled approach to code-switching, where teachers used L1 judiciously to support learning while progressively increasing English use to promote fluency. The study contributed to the ongoing debate on the pedagogical value of code-switching, highlighting its potential as a flexible instructional strategy when applied thoughtfully within learners’ sociocultural and linguistic contexts.